If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1x = 3y + -6 Reorder the terms: 1x = -6 + 3y Solving 1x = -6 + 3y Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Divide each side by '1'. x = -6 + 3y Simplifying x = -6 + 3y
| 4x-6y=-50 | | 2a+3b=34 | | -2.4x+0.1y=6.7 | | 3x+(-6)+8= | | s=k | | 1.2y+1.2=-2.4 | | -2.4x+0.1y= | | Y-4(-2)=3 | | 7(x-4)=9x-3(x+12) | | 13x-39y=-78 | | 7+-3b=1 | | 10-5x+7x=2x+10 | | 73=5w+17 | | 5x+5-4x=3 | | solvinghf=2gh | | x+x*3+x*9=195 | | Y=200x+48 | | 4x+6x-3x-8x= | | 5y+5-4y=3 | | 8d=150+2d | | 2(d-4)=-2*d+8 | | 5x+5-4y=3 | | 75.00+0.10x= | | (3x+5)=8x | | 6x^2-17x+4= | | r=2g+2vforg | | (x-3)/5=6/10 | | 6x+5=-3 | | (20x-5)=(15x+15) | | 2+2x+8=0 | | a^8b^5-a^4b^3+a^3b^6-a^3b^3=0 | | 4z-5=-29 |